Selective Electrochemical Pesticide Sensor Modified with Click Electrochemistry between Cobaltphthalocyanine and 4-Azidoaniline - KOCA, ATIF (ELECTROCHEMICAL SOC INC, 2014)
A selective and highly sensitive electrochemical pesticide sensor (EPS) was constructed for the first time in this study with a new electrode modification technique, called click electrochemistry (CEC). With CEC technique, a cobalt phthalocyanine bearing alkyne terminal substituents (TA-CoPc) was electrochemically bonded to the azide groups of poly 4-azidoaniline (ANI-N-3) which was previously electropolymerized on a glassy carbon electrode and consequently a modified electrode (GCE/PANI-N-3/TA-CoPc was constructed. Constructed BPS electrode was characterized with electrochemical, electrochemical impedance spectroscopy (EIS) and UV-Vis spectroscopy techniques. Voltammetric analysis of the electrode indicated that EPS electrode gave aniline and CoPc based redox couples in aqueous solution, which are the fundamental requirements of a functional material for the electrochemical sensor applications. Thus this electrode was tested as a possible BPS with SWV, EIS and double potential step chronocoulometry (DPSCC) techniques. BPS electrode gave different redox peaks during interaction with different pesticides which indicated selectivity for especially eserine, parathion, carbaryl, and carbofuran pesticides. EPS electrode was introduced as an excellent selective and reproducible electrochemical pesticide sensor. (C) 2014 The Electrochemical Society. All rights reserved.
Keywords: ACETYLCHOLINESTERASE-BASED BIOSENSORS; MOLECULARLY IMPRINTED POLYMER; COBALT PHTHALOCYANINE; ORGANOPHOSPHATE PESTICIDES; CARBAMATE PESTICIDES; MODIFIED ELECTRODES; GOLD NANOPARTICLES; CARBON ELECTRODE; CHOLINESTERASE; QUANTIFICATION